The widespread regulation of microRNA biogenesis, function and decay - Krol, Jacek; Loedige, Inga; Filipowicz, Witold (Nature reviews. Genetics, 2010)
Key Points MicroRNAs (miRNAs) are a large family of post-transcriptional regulators of gene expression that control many developmental and cellular processes in eukaryotic organisms. Recent research indicates that miRNA regulators themselves are subject to sophisticated control at the levels of miRNA metabolism and function. Transcription of miRNA genes is regulated similarly to that of protein-coding genes, and is a major level of control responsible for tissue-specific or development-specific expression. miRNAs are uniquely suited to participate in autoregulatory feedback circuits owing to their potential to directly repress mRNAs that encode factors involved in miRNA synthesis. miRNA precursors are processed to mature miRNAs in two steps involving the RNase III family enzymes Drosha and Dicer. These maturation steps are subjects of intricate regulation (either positive or negative) by protein factors that either interact with Drosha or Dicer, or bind to miRNA precursors. Many regulators affect the processing of a broad range of miRNAs, indicating that they can modulate expression of entire gene networks. Many miRNA precursors undergo editing by adenosine deaminases that catalyse the conversion of adenosine to inosine in dsRNA segments, altering the base-pairing and structural properties of transcripts. These modifications can affect miRNA processing and can also change properties of mature miRNAs. miRNAs function in association with argonaute and glycine-tryptophan protein of 182 kDa (GW182) proteins, which are the main components of the miRNA-induced silencing complex (miRISC). As part of the miRISC, miRNAs base-pair to target mRNAs and induce their translational repression or deadenylation and degradation. miRISCs interact with many additional factors that are required for miRNA function or for modulation. The mode of action for most of the accessory proteins remains unknown. Argonaute and GW182 proteins, and also some accessory factors, are subject to post-translational modifications that may regulate their activity. The activity of miRISCs interacting with the mRNA 3′-UTR can be modulated by RNA-binding proteins interacting with the same mRNA. The same RNA-binding protein can, depending on the mRNA or cellular context, either prevent or activate miRISC repression. It is generally thought that miRNAs are highly stable molecules. However, in some cell types, in particular in neurons, miRNAs decay very rapidly and their turnover is dependent on neuronal activity. The stability of mature miRNAs may be regulated by the untemplated addition of adenosine or uracil residues to the miRNA 3′ end. miRNA repression may involve specific cellular structures or compartments such as processing bodies or multivesicular bodies. In neurons, selected miRNAs are enriched at distal sites in dendrites, and evidence exists to suggest that synaptic stimulation is accompanied by reactivation of mRNAs targeted by miRNAs at dendritic spines. MicroRNAs are post-transcriptional regulatory molecules that control many developmental and cellular processes. Recent studies have revealed that microRNAs themselves are subject to sophisticated control at various levels, including biogenesis, function and decay. Such regulation greatly contributes to the specific functions of microRNAs. MicroRNAs (miRNAs) are a large family of post-transcriptional regulators of gene expression that are ∼21 nucleotides in length and control many developmental and cellular processes in eukaryotic organisms. Research during the past decade has identified major factors participating in miRNA biogenesis and has established basic principles of miRNA function. More recently, it has become apparent that miRNA regulators themselves are subject to sophisticated control. Many reports over the past few years have reported the regulation of miRNA metabolism and function by a range of mechanisms involving numerous protein–protein and protein–RNA interactions. Such regulation has an important role in the context-specific functions of miRNAs.